Coherent current states in a two-band superconductor - Yerin, Y.S.; Omelyanchouk, A.N. (Физика низких температур, 2007)
Homogeneous current states in thin films and Josephson current in superconducting microbridges are
studied within the frame of a two-band Ginzburg–Landau theory. By solving the coupled system of equations
for two order parameters the depairing current curves and Josephson current-phase relation are calculated
for different values of phenomenological parameters and . Coefficients and describe the coupling
of order parameters (proximity effect) and their gradients (drag effect), respectively. For definite values of
parameters the dependence of current j on superfluid momentum q contains local minimum and corresponding
bi-stable states. It is shown that the Josephson microbridge from two-band superconductor can demonstrate
-junction behavior.